Impact of Type 2 Diabetes Mellitus on Apical Periodontitis Size, Endotoxin Levels, and Bacterial Load in Root Canals with Necrotic Pulp - Barros, Mirela Cesar; Velasquez-Espedilla, Evelyn Giuliana; Oliveira, Luciane Dias de [UNESP]; Gomes, Brenda Paula F A; Duarte, Marco Antônio Hungaro; Negrato, Carlos Antônio; Andrade, Flaviana Bombarda (Elsevier, 2025)
INTRODUCTION: This clinical study was conducted to describe the endodontic microbiological profile of teeth with apical periodontitis in patients with type 2 diabetes mellitus (T2DM), focusing on bacterial count and endotoxin levels found in primary infection, as well as the size of periapical lesions, determined by cone-beam computed tomography (CBCT) analysis. METHODS: Thirty-four patients were selected and divided into 2 groups: 17 with T2DM and 17 nondiabetic controls. Anamnesis, clinical examinations, and radiographic evaluations were performed. Root canal samples were collected using sterile/pyrogen-free paper tips. Endotoxins were quantified using limulus amoebocyte lysate assay, and bacterial counts (colony forming units/mL) were determined using anaerobic culture techniques. The periapical status of the teeth was assessed using the CBCT periapical index. Data were analyzed using Pearson correlation, simple linear regression, t-tests, and Chi-square tests (P < .05). RESULTS: A larger size of periapical lesions (CBCT periapical index ≥4) was observed in patients with T2DM (64.8%) compared to controls (17.7%) (P < .05). There was a significant increase in the number of bacteria by culture and endotoxin levels in diabetic patients. A positive correlation was found between elevated endotoxin levels and the diameter of periapical lesions (P < .05). CONCLUSIONS: This study supports the hypothesis that T2DM is associated with a greater microbial load and higher endotoxin levels, contributing to more severe periapical bone destruction, which may negatively affect endodontic treatment outcomes in these patients.